Inhibition of NMDA receptors and other ion channel types by membrane-associated drugs - Neureiter, Elizabeth G.; Erickson-Oberg, M. Quincy; Nigam, Aparna; Johnson, Jon W. (Frontiers in Pharmacology, 2025)
N-methyl-D-aspartate receptors (NMDARs) are ligand-gated ion channels present at most excitatory synapses in the brain that play essential roles in cognitive functions including learning and memory consolidation. However, NMDAR dysregulation is implicated in many nervous system disorders. Diseases that involve pathological hyperactivity of NMDARs can be treated clinically through inhibition by channel blocking drugs. NMDAR channel block can occur via two known mechanisms. First, in traditional block, charged drug molecules can enter the channel directly from the extracellular solution after NMDAR activation and channel opening. Second, uncharged molecules of channel blocking drug can enter the hydrophobic plasma membrane, and upon NMDAR activation the membrane-associated drug can transit into the channel through a fenestration within the NMDAR. This membrane-associated mechanism of action is called membrane to channel inhibition (MCI) and is not well understood despite the clinical importance of NMDAR channel blocking drugs. Intriguingly, a hydrophobic route of access for drugs is not unique to NMDARs. Our review will address inhibition of NMDARs and other ion channels by membrane-associated drugs and consider how the path of access may affect a drug’s therapeutic potential.